Survey Of The Effectiveness Of Online Learning Processes In Sports Massage Courses - Kurniawan, Ari Wibowo; Widigdya, Argadianto (UNIVERSITAS NEGERI MAKASSAR, 2021)
The purpose of this study is to determine the effectiveness of the online learning process in the Sports Massage course for students of the Department of Physical Education, Health and Recreation, State University of Malang, class of 2017. This study used a quantitative descriptive research design and survey research techniques. The population used in this study were all 189 students majoring in Physical Education, Health and Recreation, State University of Malang, class of 2017. From this population, a sample of 130 people was obtained. The data in this study were obtained through a questionnaire distributed online using Google Form. There are six sub-variables assessed in this research: student learning interest, online learning excellence, online learning weaknesses, online learning facilities and infrastructure, interaction quality, and online learning prospects. Based on the results of the research and data analysis, the percentage of the overall value is 55.56%, which falls into the quite effective category, so it can be concluded that the process of online learning in the Sports Massage course is quite effective in being applied to students majoring in Physical Education, Health and Recreation, State University of Malang, class of 2017.